Selenoprotein P regulates 1-(4-Chlorophenyl)-benzo-2,5-quinone induced oxidative stress and toxicity in human keratinocytes - Xiao, Wusheng (2013)
Polychlorinated biphenyls and their metabolites are environmental pollutants that are believed to have adverse health effects presumably by inducing oxidative stress. To determine if 1-(4-Chlorophenyl)-benzo-2,5-quinone (4-ClBQ: metabolite of 4-monochlorobiphenyl, PCB3) induced oxidative stress is associated with changes in the expression of specific antioxidant genes, mRNA levels of 92 oxidative stress-response genes were analyzed using TaqMan(®) Array Human Antioxidant Mechanisms (Life technologies), and results were verified by performing quantitative RT-PCR assays. The expression of selenoprotein P (sepp1) was found to be significantly downregulated (8–10-fold) in 4-ClBQ treated HaCaT human skin keratinocytes, which correlated with a significant increase in MitoSOX oxidation. Overexpression of Mn-superoxide dismutase, catalase, or treatment with N-acetyl-L-cysteine suppressed 4-ClBQ-induced toxicity. Sodium selenite supplementation also suppressed 4-ClBQ-induced decrease in sepp1 expression, which was associated with a significant inhibition in cell death. Furthermore, HaCaT cells overexpressing sepp1 were resistant to 4-ClBQ induced oxidative stress and toxicity. These results demonstrate that SEPP1 represents a previously unrecognized regulator of PCB induced biological effects. These results support the speculation that selenoproteins can be an attractive countermeasure for PCB induced adverse biological effects.